Implementation of Supplement Teaching Materials Based on Problem Based Learning to Improve Concept Mastery and Health Care Attitudes - Elis Risyanti; Lisdiana Lisdiana; Wiwi Isnaeni (Universitas Negeri Semarang, 2022)
Learning with the 2013 curriculum requires the use of various learning resources, learning media and teaching materials that vary to support the learning process.. These results of the students being constrained in learning the material because the material in the book is too little, so it is difficult to understand. This study aims to analyze the effect of PBL-based supplementary teaching materials on the concept mastery and health care attitude. This study used a quasi-experimental method with nonequivalent control group research design. The samples used were VA and VB SDIT Tazkia Insani classes. The instruments used were tests, attitude scale sheets, observation sheets, interviews, and notes. The results showed that after being given action in the experimental class, students' concept mastery and health care attitudes increased. The conclusions of this study are 1) PBL-based supplementary teaching materials on human respiration affect mastery of concepts. 2) Supplements of PBL-based teaching materials on human respiration influence health care attitudes. 3) Supplements of PBL-based teaching materials on human respiration have a received a positive response from teachers and students. 4) Supplements of PBL-based teaching materials on human respiration have a relationship between concept mastery and health care attitudes